Optimization of the thermal regime and reliability of radio-electronic block - Никитчук, А.В.; Уваров, Б.М. (Radiotekhnika, 2016)
The problem of maximizing the reliability of electronic block and its cells under the action of thermal destabilizing factors is considered. The algorithms for optimal placement of the cells in the block, that provides a minimum temperature and the maximum reliability of elements of the electronic structure, are proposed.  Software modules that implement these algorithms are developed and described, the results of simulation obtained by these modules for real designs of radio electronic blocks are presented.